A Link between Parental Psychopathology and Preschool Depression: Take Care of Parents to Take Care of Children - Melania Martucci; Franca Aceti; Nicoletta Giacchetti; Veronica Scarselli; Carla Sogos (MDPI AG, 2023)
There is a lot of evidence in the literature showing that early-onset depression determines an emotional and cognitive vulnerability for psychiatric disorders in subsequent years. AIMS: The first aim of this outcome research was to analyze the impact of parental support treatment in a sample of depressed preschool children divided into two groups of comparison (under-reactive and over-reactive) through evolution in the Clinical Global Impression (CGI). The second aim was to analyze the correlation between the presence of parental psychopathology and the severity of children's disorders. METHODS: Our clinical sample consisted of 32 preschool-age children with a final diagnosis of MDD. The children's assessment included a psychiatric assessment to establish a diagnosis of MDD, confirmed by means of a semi-structured interview, which was administered again one month after the end of parental treatment. All the parents began a six-month parent training treatment conducted by experienced child psychiatrists, whereas children were not treated. During this period, the Clinical Global Impression Scale (CGI) was filled out monthly in order to observe the evolution of the children's disorders. Results: Post-hoc tests showed a significant difference from before the treatment to after the treatment only in the over-reactive group (p = 0.00). Regarding parental psychiatric disorders, in the over-reactive group, only 3 children had no parents with psychopathology. In the under-reactive group, no child lacked a parent with psychopathology. Conclusion: Parent training treatment seems to be a valid intervention to improve preschool depression, especially in over-reactive groups, and to prevent dysfunctional parental styles connected to parental psychopathology.